IMPLEMENTASI MODEL PAKEMI BERBASIS LINGKUNGAN DALAM MENINGKATKAN HASIL BELAJAR DAN LITERASI SAINS IPAS DI KELAS V SEKOLAH DASAR - Nadiroh, Iroh; Khoimatun; Hadiansah, Dede (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes and science literacy of students in IPAS lessons, particularly in Grade V of SDN 2 Segeran Kidul. This was due to several factors, one of which was the inappropriate use of learning models and methods. The purpose of this study was to describe the observation sheet for the application of the PAKEMI model, student learning outcomes and science literacy in IPAS lessons with the application of the PAKEMI model. This study used Kemmis and Mc Taggart's Classroom Action Research (CAR) design, which was carried out in 3 cycles with 34 fifth-grade students at SDN 2 Segeran Kidul as the research subjects. The data collection techniques used were observation, tests, and questionnaires. The results of the study included 1) determining the application of the PAKEMI model, 2) determining the improvement in learning outcomes, and 3) determining the improvement in science literacy. In cycle I, the learning outcomes received a percentage of 44%. Then, there was an increase in cycle II to 85%. Then, in cycle III, it reached 91%. In cycle I, science literacy received a percentage of 69% in the moderate category. Then, it increased in cycle II to 85.6% in the high category. Then, in cycle III, it reached 93.3%.